Psychological investigation of the structure of paranoia in a non-clinical population. - Freeman, D; Garety, P; Bebbington, P; Smith, B; Rollinson, R; Fowler, D; Kuipers, E; Ray, K; Dunn, G (2005)
BACKGROUND: Previous studies of paranoia have assessed only limited numbers of paranoid thoughts, and have not considered the experience from a multidimensional perspective or examined the relationship between different suspicious thoughts. AIMS: To assess a wide range of paranoid thoughts multidimensionally and examine their distribution, to identify the associated coping strategies and to examine social-cognitive processes and paranoia. METHOD: Six questionnaire assessments were completed by 1202 individuals using the internet. RESULTS: Paranoid thoughts occurred regularly in approximately a third of the group. Increasing endorsement of paranoid thoughts was characterised by the recruitment of rarer and odder ideas. Higher levels of paranoia were associated with emotional and avoidant coping, less use of rational and detached coping, negative attitudes to emotional expression, submissive behaviours and lower social rank. CONCLUSIONS: Suspiciousness is common and there may be a hierarchical arrangement of such thoughts that builds on common emotional concerns.